Impulse Response (IR) of a Given Continuous Time (CT) System in Digital Signal Processing - T. C. Manjunath; Kavita S. Guddad; Kumar Puttaswamy; Pavithra G. (Journal of Electronic Design Engineering, 2021)
In this paper, the impulse response of a given continuous-time system using MATLAB is presented. The main aim is to find the impulse response h(n) of the given LTI system whose response y(n) to an input x(n) is given. A Linear Time-Invariant (LTI) system is taken for reference. An input of x(n) is given to the LTI system. The CT system takes the input signal, processes it & gives the result as the output signal. The input is called the excitation & the output is called the response. Since the input is an impulse signal, the output response is called the impulse response, i.e., the response of a signal due to an impulse input is called the impulse response. Here, the impulse response is generated using a code developed in Matlab & the simulation results show the effectiveness of the programming approach developed.